Community-Based Cardiac Rehabilitation To Improves Medication Adherence in Stable Coronary Artery Disease - Tonny Adriyanto; Cholid Tri Tjahjono; Mohammad Saifur Rohman; Sasmojo Widito; Ardian Rizal (Universitas Brawijaya, 2020)
Cardiovascular disease contributes to 48% of deaths in the world. A cohort study at the Harapan Kita National Heart Center and 5 Indonesia hospitals in 2006 showed that the death rate due to heart disease in hospitals was around 6-12%. Rehospitalization rate reached 29% and the all-out expense of INA-CBG claimed for inpatient was Rp 42.4 trillion. The major problem causing rehospitalization was poor compliance to medication in coronary artery disease (CAD) patients. Education to improve compliance has been known not only reduced rehospitalization rate but also improve quality of life. In these review the author discussed the efficacy of community based cardiac rehabilitation for rehospitalisation reduction dan quality of life improvement.